Transcriptome profiling, physiological, and biochemical analyses provide new insights towards drought stress response in sugar maple (Acer saccharum Marshall) saplings - Mulozi, Lungowe; Vennapusa, Amaranatha R.; Elavarthi, Sathya; Jacobs, Oluwatomi E.; Kulkarni, Krishnanand P.; Natarajan, Purushothaman; Reddy, Umesh K.; Melmaiee, Kalpalatha (Frontiers in Plant Science, 2023)
Sugar maple (Acer saccharum Marshall) is a temperate tree species in the northeastern parts of the United States and is economically important for its hardwood and syrup production. Sugar maple trees are highly vulnerable to changing climatic conditions, especially drought, so understanding the physiological, biochemical, and molecular responses is critical. The sugar maple saplings were subjected to drought stress for 7, 14, and 21 days and physiological data collected at 7, 14, and 21 days after stress (DAS) showed significantly reduced chlorophyll and Normalized Difference Vegetation Index with increasing drought stress time. The drought stress-induced biochemical changes revealed a higher accumulation of malondialdehyde, proline, and peroxidase activity in response to drought stress. Transcriptome analysis identified a total of 14,099 differentially expressed genes; 328 were common among all stress periods. Among the differentially expressed genes, transcription factors (including NAC, HSF, ZFPs, GRFs, and ERF), chloroplast-related and stress-responsive genes such as peroxidases, membrane transporters, kinases, and protein detoxifiers were predominant. GO enrichment and KEGG pathway analysis revealed significantly enriched processes related to protein phosphorylation, transmembrane transport, nucleic acids, and metabolic, secondary metabolite biosynthesis pathways, circadian rhythm-plant, and carotenoid biosynthesis in response to drought stress. Time-series transcriptomic analysis revealed changes in gene regulation patterns in eight different clusters, and pathway analysis by individual clusters revealed a hub of stress-responsive pathways. In addition, qRT-PCR validation of selected DEGs revealed that the expression patterns were consistent with transcriptome analysis. The results from this study provide insights into the dynamics of physiological, biochemical, and gene responses to progressive drought stress and reveal the important stress-adaptive mechanisms of sugar maple saplings in response to drought stress.